Kesejahteraan dan Bela Negara di Indonesia: Kajian Literatur Perspektif Kewargaan - Nebula Fauzan Hasani; Ana Sabhana Azmy (Universitas Islam Negeri (UIN) Salatiga, 2025)
This research explores the relationship between state defence awareness, citizenship, and welfare based on an analysis of literature over the past ten years. Citizenship is understood through the perspective of T.H. Marshall's theory that integrates civil, political, and social rights, as well as Hiariej and Stokke's approach that sees citizenship as a dynamic social practice. This research uses the literature study method by collecting literature reviews over the past 10 years related to welfare and state defence. The results of the analysis show that the fulfilment of social rights, such as access to education and health, is an important element in strengthening active citizen participation in state defence. Poverty alleviation through inclusive policies proves to be a prerequisite for strengthening inclusive citizenship and national solidarity. In terms of education, civic education plays an important role in instilling values of nationalism, solidarity, and social responsibility, which expands the meaning of state defence to the social and economic spheres. Thus, the results of this study emphasise the importance of integration between welfare, citizenship, and state defence to create a just, cohesive, and resilient society.